The Komunikasi Partisipatif Antara Sekolah Dan Keluarga Dalam Pendidikan Anak Usia Dini di RA At Thoriq Batam: Chidhood Education - Darma, Darmawati; Maya Inayati Sari; Yuli Fatimah Warosari; Nurhayati (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early childhood education plays a crucial role in shaping a child's developmental foundation. In an effort to understand how early childhood education can be enhanced, this research delves into the theme of "Participatory Communication Between School and Family in Early Childhood Education at RA At Thoriq Batam." The research employs a qualitative approach and analyzes the dynamics of communication and family involvement within the context of early childhood education. This research underscores the significance of effective communication between the school and families in establishing a balanced educational environment. The research findings reveal various strategies and factors influencing the level of family involvement in early childhood education. These findings provide a profound insight into how participatory communication can strengthen collaboration between the school and families, ultimately yielding positive impacts on the development of young children. The implications of this research underscore that efforts to build and maintain effective communication between schools and families must be a priority in the context of early childhood education.